Ascension of larks [large type] - Linden, Rachel (Center Point Large Print, 2017)
"When globetrotting photographer Magdalena Henry loses the only man she's ever loved, she risks her stellar career to care for his widow and young children on a remote island in the Pacific Northwest"--